Variety of Eating Patterns Consistent with Glycemic Control with Ongoing Support - Kuznar, Wayne (MD Conference Express, 2014)
In general, a variety of eating patterns are acceptable for the management of diabetes, as long as follow-up encounters and ongoing support are implemented. This article discusses the need for medical nutrition counseling as a component of an overall management strategy to achieve treatment goals in adults with type 1 diabetes mellitus or type 2 diabetes mellitus.